A Repeatable Dual‐Encryption Platform from Recyclable Thermosets with Self‐Healing Ability and Shape Memory Effect. (16th June 2022) - Yang, Xi; Guo, Meiling; Yan, Jiao; Wang, Li; Zhao, Chuanxia; Xiang, Dong; Li, Hui; Lai, Jingjuan; Li, Zhenyu; Ahmed, Abbas; Sun, Luyi; Wu, Yuanpeng
Abstract: Repeatable dual‐encryption platforms, coupled with a strong protective capacity for stored information, are highly desirable for current data security but still a challenge to be realized. Herein, a new type of thermoset‐based repeatable dual‐encryption platform is designed to fulfill the challenge. Through introducing dynamic boroxine bonds and hydrogen bonds within the thermoset, self‐healing, recyclability, and shape‐memory properties can be achieved. Given the shape memory behavior of this thermoset, encryption data within complex 3D structures can be realized. Thus, shape recovery is inevitable for the decryption, providing strong protection for encrypted data. Furthermore, the encrypted data can be protected by showing misleading information before true information during the decryption process, which is caused by the different analogous "LEGO" assembly sequences of thermosets that induces different hydrophobic association interactions. The decrypted information can be erased by heating, realizing the repeatable encryption/decryption. Additionally, the thermosets can be efficiently recycled. This strategy opens up a smart prospect for high level dual‐encryption platform. Abstract : A novel recyclable thermoset‐based repeatable dual‐encryption platform is designed. 2D data are made by a "LEGO"‐inspired assembly method based on the self‐healing property and different hydrophobic associations of thermosets. The 2D data are further hidden in complex 3D structures and protected by misleading information, showing an intelligent prospect for high data security.